Primary Ovarian Leiomyoma—A Common Tumor at an Uncommon Site - Pradeep, Aswathy; Bhat, Shubha Padmanabha; Nandan, Neetha; Laxminarayana, Kishan Prasad Hosapatna; Kaliyat, Sajitha; Venugopala, Kishan Prasad Holalkere (Journal of Health and Allied Sciences NU, 2019)
Leiomyoma is a benign mesenchymal tumor that commonly occurs in the uterus, ovary being a rare site. Ovarian leiomyomas constitute 0.5 to 1% of all benign tumors. They probably arise from the smooth muscle cells in the ovarian hilar blood vessels. They occur most commonly in premenopausal women. We report a case of primary ovarian leiomyoma in a 39-year-old female patient.
Keywords: leiomyoma; ovary; smooth muscle tumor; histopathology; Masson’s trichrome stain